Impact of cardiac- and noncardiac-related conditions on adverse outcomes in patients hospitalized with acute myocardial infarction. (24th May 2019) - Tisminetzky, Mayra; Gurwitz, Jerry H; Miozzo, Ruben; Gore, Joel M; Lessard, Darleen; Yarzebski, Jorge; Goldberg, Robert J
Background: To examine the impact of cardiac- and noncardiac-related conditions on the risk of hospital complications and 7- and 30-day rehospitalizations in older adult patients with an acute myocardial infarction (AMI). Methods and Results: The study population consisted of 3863 adults aged 65 years and older hospitalized with AMI in Worcester, Massachusetts, during six annual periods between 2001 and 2011. Individuals were categorized into four groups based on the presence of 11 previously diagnosed cardiac and noncardiac conditions. The median age of the study population was 79 years and 49% were men. Twenty-eight percent of patients had two or less cardiac- and no noncardiac-related conditions, 21% had two or less cardiac and one or more noncardiac conditions, 20% had three or more cardiac and no noncardiac conditions, and 31% had three or more cardiac and one or more noncardiac conditions. Individuals who presented with one or more noncardiac-related conditions were less likely to have been prescribed evidence-based medications and/or to have undergone coronary revascularization procedures than patients without any noncardiac condition. After multivariable adjustment, individuals with three or more cardiac and one or more noncardiac conditions were at greatest risk for all adverse outcomes. Conclusions: Older patients hospitalized with AMI carry a significant burden of cardiac- and noncardiac-related conditions. Older adults who presented with multiple cardiac and noncardiac conditions experienced the worse short-term outcomes and treatment strategies should be developed to improve their in-hospital and post-discharge care and outcomes.